#TITLE_ALTERNATIVE# - (NIM 23297509); Pembimbing: Dr. Parouli Pakpahan, HENDRI
Analysis of distribution impuls voltage at the end of tranfformator windings and their respons on full impuls standart waveform and chopped impuls standart waveform are proposed in this research. The experimental datas are compared with EMTP simulation. For t < 1.0us, there are some diference values. For t > 2.0 us, The expemental datas close with the simulation ones. So, it can be said that the EMTP simulation circuit can substitute for the real circuit well. Transformator winding contruction and its isolation level (Cs and Cg) affect the distribution of tansformator voltage at transient period. The highest voltage gradient happens on the nearest winding with high voltage side, with IBC-71 standart current surge (8/20 us). The most important result of this research is the simulation has less self-confidence (EMTP simulation voltage is higher than experimental one). Although it is difficult to close with real condition at transient period, it is not quite bad to be used as an experimental substitution for knowing current surge respon of winding.